Effects of free play or artificial rules on young soccer players’ individual tactical behaviour: a one-by-one analysis - Gonzalez-Artetxe, Asier; Folgado, Hugo; Pino-Ortega, José; Rico-González, Markel; Los Arcos, Asier (Biology of Sport, 2023)
This study assessed the effects of playing freely and introducing artificial rules on individual tactical behaviour during the team-possession game phase in two youth soccercategories. Thirty-two developmental players from U-14 and U-16 teams participated in the study, which consisted of four identical training sessions and two test sessions performed before and after the intervention. Each team was divided into two balanced groups, free-play and conditioned, that faced each other during three eight-a-side games (Gk + 7 vs 7 + Gk) in all training sessions. The free-play groups played freely, while the conditioned ones did so constrained by artificial rules. Individual tactical behaviour was assessed during a non-constrained eight-a-side match by the distance to centroid, spatial exploration index, their entropy measures, and the regularity of each player’s displacement on the length and width of the pitch using a local positioning system. In addition to the average outcomes of all the players all together, the one-by-one analysis considered the mean values of each player to appraise individual responses. While the average outcomes of all the players in both groups and categories barely changed (Cohen’s d ≤ small), with a very high inter-player variability, the one-by-one analysis revealed that the training intervention affected each player’s tactical behaviour differently. Introducing artificial rules decreased and raised considerably (Cohen’s d ≥ moderate) in-width and exploratory regularities of most U-14 and U-16 players, respectively. Therefore, assessing the training effects of game-based interventionsfrom the individual to the whole team may provide unique and meaningful insight regarding the tactical competence of each player.